The Effect of Age on Egg Production, Hatchability and Egg Quality Characteristics in Pheasants (Phasianus colchicus) - Esen, Fikret; Ozbey, Orhan; Genc, Feride (Medwell Online, 2010)
The aim of this study was to determine egg production, hatchability and egg quality characteristics in ring-necked pheasants at the different ages (1, 2 and 3 years old) of hatching. The age of pheasant was determined to affect egg production and egg weight significantly in pheasants (p<0.05). While the highest egg production was obtained at the 2 years old of pheasant (53.27%), the highest mean egg weight was obtained at the age of three years old of pheasant (33.83 g). The significant differences between hatchability of total eggs, fertility rate and hatchability of fertile eggs at various ages of pheasants suggested that the hatching season is significantly related to the hatchability characteristics (p<0.01). The differences between the shape index, egg shell weight, egg shell thickness, yolk weight and index, albumen weight and index and haugh unit were significant for various age groups (p<0.05, p<0.01) and the effect of age on these features was significant (p<0.05, p<0.01). It was concluded that there is no disadvantage in keeping the ring-necked pheasants for breeding for three years and it may be cost-effective for breeders possessing a lower number of brood pheasants. It was found that using ring-necked pheasants for a maximum of two years for breeding has the best outcome if there is no breeding problem.
Keywords: Pheasant; age; egg production; hatchability; egg quality characteristics; Turkey